2005
DOI: 10.1557/jmr.2005.0188
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Testing for Fracture of Oxide Films

Abstract: The mechanical properties of thermally grown oxide films on various aluminum substrates were tested using nanoindentation. A sudden discontinuity, indicative of film fracture, was observed upon loading portion of the load-depth curve. The 63-nm-thick films were determined to have ultimate strengths between 4.8 and 8.9 GPa. The ultimate stress is a superposition of the bending and membrane stress. The stress intensity at fracture for each of the films was developed by approximating the resulting bending moment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This abrupt change during loading can be connected to two phenomena: (1) the transition regime from elastic to elasto-plastic deformation of the material [31] or (2) the fracture of the oxide film due to the indentation stress intensity and the brittleness of the film [32][33][34]. In case 1, Hertz's theory represented by the power law: L¼ Kh 3/2 , where K is a parameter related to the elastic modulus, must be verified before the pop-in event.…”
Section: Indentation Experimentsmentioning
confidence: 99%
“…This abrupt change during loading can be connected to two phenomena: (1) the transition regime from elastic to elasto-plastic deformation of the material [31] or (2) the fracture of the oxide film due to the indentation stress intensity and the brittleness of the film [32][33][34]. In case 1, Hertz's theory represented by the power law: L¼ Kh 3/2 , where K is a parameter related to the elastic modulus, must be verified before the pop-in event.…”
Section: Indentation Experimentsmentioning
confidence: 99%
“…First, the localized surface Ta 2 O 5 scale can experience basic/acidic dissolution to form TaO 3 − or Ta 4 O 11 2− /Ta 5+ ions, and the reactions can generate a large number of volatile products, thus fracturing the corrosion scale and leading to the generation of defects in it, such as pores and cracks. Second, the transformation from Ta to oxides can cause a huge volume expansion; for example, based on the crystal parameters of Ta, Ta 2 O 5 , and Na–Ta–O, one Ta atom transforming to Ta 2 O 5 , NaTaO 3 , and Na 2 Ta 4 O 11 expands the volume by 2.59, 3.63, and 3.06 times, respectively, leading to a stress generated in the corrosion scale and at the Ta interface . As the scale thickness increases, the stress in the corrosion scale increases; thus, the corrosion scale breaks and detaches from the surface when the stress increases to a certain level (Figure e,f).…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al [3] revealed the mechanical properties and deformation mechanism of gold nanowires under different strain rates by the molecular dynamics method. Morasch et al [4] tested the mechanical properties of oxide films by nano-indentation, and obtained the stress intensity at the fracture point. Kim et al [5] proved that the compression on sulfide film containing residual compressive stress could improve the elastic modulus of the film and increase the fracture resistance.…”
Section: Introductionmentioning
confidence: 99%